2018
DOI: 10.1111/cei.13183
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cells are epigenetically cytotoxic with signs of exhaustion in human urinary bladder cancer

Abstract: SummaryTissue‐resident memory T (TRM) cells are CD8+ T lymphocytes that reside in the tissues, including tumours. This T cell subset possesses a magnitude of cytotoxicity, but its epigenetic regulation has not been studied. Here, we investigate the impact of perforin DNA methylation in TRM cells and correlate it with their functional potential. Fifty‐three urothelial urinary bladder cancer (UBC) patients were recruited prospectively. The DNA methylation status of the perforin gene (PRF1) locus in TRM cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…47 In addition, a high number of T RM cells infiltrating the tumors is associated with lower tumor stage in patients with UBC. 48 In contrast, the accumulation of T RM cells in melanoma tumors has not been associated with prolonged survival or a better prognosis, suggesting that T RM cells are associated with a better prognosis in some cancers but not in others 106,107 ; T RM cells may have different local anti-tumor responses in different malignancies.…”
Section: Cd8 + T Rm Cells In Anti-tumor Immunitymentioning
confidence: 97%
See 2 more Smart Citations
“…47 In addition, a high number of T RM cells infiltrating the tumors is associated with lower tumor stage in patients with UBC. 48 In contrast, the accumulation of T RM cells in melanoma tumors has not been associated with prolonged survival or a better prognosis, suggesting that T RM cells are associated with a better prognosis in some cancers but not in others 106,107 ; T RM cells may have different local anti-tumor responses in different malignancies.…”
Section: Cd8 + T Rm Cells In Anti-tumor Immunitymentioning
confidence: 97%
“…46 CD103 + CD39 + tumor-infiltrating CD8 + T cells have been found for six different malignancies including melanoma, lung cancer, head and neck squamous cell carcinoma (HNSCC), ovarian cancer, and rectal cancer, 47 and high numbers of perforin-expressing T RM cells are found in patients with urothelial urinary bladder cancer (UBC). 48 These findings indicate that (1) there may be substantial phenotypic heterogeneity among T RM cell subsets; (2) the tissue microenvironment and infection route can contribute to the regulation of phenotype and function of these cells; (3) phenotypic markers of T RM cells may differ between humans and mice; and (4) limitations in experimental techniques may confound our knowledge of T RM populations; cytometric identification based on phenotypic markers sometimes cannot represent a whole population. Therefore, identification of T RM cells based solely on the coexpression of CD69 and CD103 may not reliably identify all T RM cells.…”
Section: Signature Phenotypes Of Cd8 + T Rm Cells In Various Tissuesmentioning
confidence: 98%
See 1 more Smart Citation
“…A summary of most recent studies addressing combination strategies between epigenetics and immune environment in BlCa is presented in Table 1 [54][55][56][57][58][59][60][61][62][63][64]. Some studies have focused on obtaining methylation-based biomarkers with predictive value, namely concerning response to BCG-therapy [55][56][57].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Bergman et al [58] showed that an assessment of CD4+-cell lineage commitment by looking at specific CpGs methylation status could predict the outcome of BlCa patients, with demethylation of those sites (which include FOXP3, IFNG, IL13, and IL17A) associating with lower stage and, importantly, better response to neoadjuvant chemotherapy. Moreover, Hartana et al [59] explored the perforin gene PRF1, demonstrating that tissue-resident CD8-positive T cells show demethylation of this gene promoter, correlating with its higher expression, hence with more cytotoxic ability. Finally, Ramakrishnan et al [62] focused on EZH2 inhibition and its effects on the immune environment.…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%